2021
DOI: 10.3389/fmed.2021.732410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of the Lactate/Albumin Ratio and Lactate/Albumin Ratio × Age Score in the Assessment of Prognosis in Patients With Sepsis

Abstract: Objective: To examine the clinical significance of the blood lactate (Lac)/serum albumin (Alb) ratio and the Lac/Alb × age score for assessing the severity and prognosis of patients with sepsis.Methods: A total of 8,029 patients with sepsis, aged >18 years were enrolled between June 2001 to October 2012 from the latest version of the Medical Information Mart for Intensive Care III (MIMIC-III v.1.4). The general data of the patients were obtained from hospital records and included gender, age, body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
(27 reference statements)
1
13
2
2
Order By: Relevance
“…In our study, the prognostic accuracy of LAR for 30-day mortality was good, with an AUROC of 0.737 (95% CI 0.656-0.818), similar to those described in other studies (AUROC 0.61 to 0.869) (7,10,13). Bou et al (7), in a study with 1381 patients in the ED, evaluate sensibility and speci city, with poorer results than our study (59% and 62 % vs. 71.1% and 60.8%, respectively for Bou et al and our results).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the prognostic accuracy of LAR for 30-day mortality was good, with an AUROC of 0.737 (95% CI 0.656-0.818), similar to those described in other studies (AUROC 0.61 to 0.869) (7,10,13). Bou et al (7), in a study with 1381 patients in the ED, evaluate sensibility and speci city, with poorer results than our study (59% and 62 % vs. 71.1% and 60.8%, respectively for Bou et al and our results).…”
Section: Discussionsupporting
confidence: 89%
“…In-hospital mortality was higher in these studies with ICU patients (42.7% to 62.4% (10,13), compared to our study (9.4%), as well as 28-day mortality in one study in the ED (22.5%) (9), compared to our 30-day mortality (13.2%).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The Lac level in patients with sepsis was higher in the death group than in the survival group, suggesting that Lac levels reflect the poor prognosis. [ 33 ] However, in our study, there were no statistical differences between the two groups ( P > .05). Clinically, Lac levels are usually monitored dynamically to assess the perfusion and the patient’s response to treatment and prognosis.…”
Section: Discussioncontrasting
confidence: 72%
“…[ 22 ] A new observational study found Lac/Alb was an independent risk factor for death in patients with sepsis, and Lac/Alb × age score was more accurate and convenient for providing a general assessment of prognosis. [ 23 ] This study found that the Lac/Alb could also predict myocardial injury in elderly patients with SCAP (AUC = 0.737, 95% CI 0.620–0.834), which was better than Lac and NLR, but there were no statistical differences between the 3. The diagnostic sensitivity of Lac was 100%, but the specificity was only 40.43%, which limited its clinical application.…”
Section: Discussionmentioning
confidence: 85%